Characterization of a novel terpolymer containing maleic anhydride-co-stearyl methacrylate-co-benhely acrylate for wax inhibition application - Elganidi, Ibrahim; Elarbe, Basem s.; Norhayati, Abdullah; Norida, Ridzuan (IOP Publishing, 2019)
Wax deposition in petroleum pipelines is deliberated as one of the most severe operational issues, and extraordinary efforts have been made to remediate and prevent this flow assurance problem. Using, polymeric pour point depressants (PPD) as a wax control strategy to improve the fluidity of waxy crude oil and reduce the pour point have received significant attention. The purpose of the current research is to synthesize novel terpolymers which used as PPD and viscosity improvers. The synthesis process occurred via polymerization of stearyl methacrylate (SMA), benhely acrylate (BA), and maleic anhydride (MA) monomers using free radical polymerization method in toluene as a solvent, and (1 wt%) benzoyl peroxide (BZP) as initiator. The chemical structure of the prepared terpolymer was characterized by FTIR and NMR. Also, the crystallization behavior of paraffin wax was investigated by differential scanning calorimetry (DSC). Experimental investigations furnish that the synthesized PPD showed high yield (87%) at the concentration (1:1:1) of BA-co-SMA-co-MA. From FTIR and 1HNMR characterization results observed that maleic anhydride moiety, alkyl chain moiety, and methacrylate moiety are existing in the prepared terpolymer. Furthermore, DSC analysis showed that the glass transition temperature of the prepared terpolymer is weakly stated over a wide temperature range.